Sustainable Economics for the Anthropocene The Economic Scale of Global Boundaries (ESGB) Model - Guarnieri, Leanne; Lee-Davies, Linda (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book examines both the need for sustainable economics and the financial practices that will underpin it. The link between rising inequality and the threat to social sustainability is highlighted to create the Economic Scale of Global Boundaries model, which realigns GDP to include quantifiable environmental and social economic gains and losses. The model is applied at both the national and company level to show its practical application for policy and everyday business practice. The impacts of inequality, declining economic growth and the impending deadlines of the Sustainable Development Goals are also discussed in detail. This book aims to highlight how principles of the circular economy and ESG can be utilized to help meet net zero targets. It will be relevant to students, researchers, organizations, and policymakers interested in environmental economics and sustainability and is written to provoke predictive thinking on the global changes ahead. Leanne Guarnieri is an alumnus of Fairleigh Dickinson University, USA. She works as the Head of Data Science and Management at BounceBack Homes and is an active shareholder involved in various sustainable venture capital projects. Dr Linda Lee-Davies is Assistant Professor at Coventry University and a Visiting Faculty member at Wroxton College, Fairleigh Dickinson University, UK. With both a commercial and academic background, she undertakes fresh business assignments to research emerging trends in leadership, sustainability, and technology, ensuring students are provided with the best preparation for the global workplace. .
Chapter 1. Current Context and the Targets Ahead -- Chapter 2. Income Inequality: An Indicator of Declining Growth -- Chapter 3. The Impacts of Inequality and Effects of External Factors in Economics -- Chapter 4. Economics and Sustainability: An Introduction to the ESGB Model -- Chapter 5. The ESGB Model -- Chapter 6. The Social Layer of the ESGB Model -- Chapter 7. Aligning Economically Astute Sustainability to the 17 UN SDG Targets.-Chapter 8. Normalizing and Standardizing Circular Economy and ESG Practice with Recommendations -- Chapter 9. Towards Sustainable Economics for the Anthropocene./.
Keywords: Environmental economics; Power resources; Economics; Industrial policy; Environmental Economics; Natural Resource and Energy Economics; Political Economy of Energy; Regulation and Industrial Policy